(untitled) (Praxis Educativa, 2012)
In the last decades there have been new ideas in the scientific education fields. This discussion is complex and does not point only to changes in teaching practices On the contrary, what is in discussion has to do with the contents and the aims of teaching the sciences of the basic education m a context that has suffered deep changes in the relationships between science, technology and society and also with new ideas about teaching, learning and the extension of compulsory education In this investigation we present the different currents of opinion since the second half of the XX century Secondly, we analyze some new proposals to identify main tendencies regarding aims and contents or teaching science finally, we explore the possibilities offered by the inclusion of a historical perspective when teaching sciences and the importance of the curricular documents m this dimension.